Approaches to Teaching Agreement and Disagreement in Selected Coursebook Series - Válková, Silvie; Kořínková, Jana (Theory and Practice of Second Language Acquisition, 2023)
The article focuses on the explicit teaching of language used to express agreement and disagreement in the popular English language coursebooks English File and Navigate. It reviews the current research on teaching various aspects of polite language and politeness-sensitive speech acts and analyses and compares the explicitly taught phrases of agreement and disagreement in the two selected coursebook series, as well as the methods of their presentation and the amount of background theoretical information provided to students and teachers to facilitate their proper usage. Differences were identified not in the inventories and language representation of the explicitly taught phrases, but mainly in the background support available for students and teachers on their usage.